Literature Study - Setyabudi, Titis (Journal of English and Education (JEE), 2007)
Sometimes literature is redarded as a subject that must be in avoidance position. On other hand, there are some advantages of studying literature; it assist students to acquire a habit of observation, a sensivity to the unsaid but implied, an ability to step outside of the student own perspective to understand the perception of others.